PROCESOS PROLIFERATIVOS EN LA REGIÓN CEFÁLICA DE LOS OVINOS - Alva E., Jeanette (2002)
Macro and histopathological analyses of proliferative processes in the cephalic region of adult female sheep from a large enterprise in the central sierra of Peru are reported. Of the 14 cases studied, 10 corresponded to neoplasias, one to benign proliferative growth and 3 to inflammatory processes (chronic dermatitis). The neoplasias effected the ear lobe (n=5), eye ball (n=4) and the nostril (n=1), while the proliferative (hyperkeratotic papilloma) and chronic dermatitis cases were jeopardizing the ear lobe. Macroscopically the tumors presented exophytic semi-oval, papillomatous and semicircular growths, and all had exudate and necrotized surfaces. The neoplasias were not associated with metastasis, but histologically demonstrated diverse degrees of cellular differentiation. Of the 10 neoplasias, 6 corresponded to degree I (well differentiated) and 4 to degree II (moderately differentiated) . All the animals effected with tumors presented slight leukocytosis, generally characterized by neutrophilia, and slight to moderate lymphopenia was found in 2 of the 10 cases.